The key elements of classroom management : - McLeod, Joyce (Association for Supervision and Curriculum Development, 2003)
Three veteran teacher-authors explain the essentials: Setting up your classroom and establishing routines; Pacing the curriculum and dealing with transitions and interruptions; Preventing the most common discipline problems and effectively handling them when they occur; Selecting the right instructional strategy to fit the students and the information to be learned